The Implementation of Linear Programming in Optimizing Concrete Slab Mobilization Operations PT.XYZ - Muhammad Rilly Aka Yogi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Dumai-Malacca international Ro-Ro port connection is a strategic plan of Indonesian government to increase the national logistics distribution mode, especially in Southeast Asia regional trading activities. PT. Pelindo I, as an SOE port operator, is the candidate who will get a delegation for the implementation of this strategic program for providing port facilities to meet the needs of international crossings. This study aims to assess and optimize the internal financial aspects of PT Pelindo I as the result of the project implementation. As the company with a capital intensive character, corporate action must be able to provide good returns and benefit with clearly mitigated risks. Results show port should provide at least on moderate threshold level of occupancy. The less occupied operation will lead to financial problem along the service life. Thus, the least reliable scenario used is scenario 2 with realistic occupation level of 61%, IDR-USD currency rate of IDR.14600, and inflation rate of 3.97%, along with the recommendation for implementing subscription register method between ports and customer. The ROA and ROE result 0,83% and 0,89% respectively, and will remain positive along with revenue generation. These are considered to be effective in producing good financial performance and guarantee long-term business sustainability, while it can also optimize the absorption of service use by commodity based industries that the product will be distributed in the Southeast Asia region.